AB0149 Identification and Characterization of A Synovial Fluid Microbial DNA in Rheumatoid Arthritis Patients. (10th June 2014) - Barnetche, T.; Hubert, C.; Barre, A.; Richez, C.; Shipley, E.; Truchetet, M.-E.; Nikolski, M.; Schaeverbeke, T.
Abstract : Background: The preclinical phase of Rheumatoid Arthritis (RA) is characterized by an immunological disorder that predate the arthritis onset for several years, and is supposed to take birth in oral, respiratory or intestinal mucosa after exposure to environmental triggers. The potential role of bacteria has been reinforced by recent studies that demonstrated the link between Porphyromonas gingivalis and RA and, above that, by studies showing the influence of oral, lung or gut microbiota on RA and other inflammatory diseases. One major question is to make the connexion between joint and mucosal surface. We postulated that the onset of clinical phase of RA is related to the translocation of bacterial antigens or full bacteria from a mucosa to the joint, transferring the immunological disorder within the joint. Objectives: The aim of this study was: 1) to look for the presence of bacterial DNA in synovial fluid (SF) of RA patients and in SF from osteoarthritis (OA) patients.- 2) to characterize the profile and the diversity of identified organisms in both groups. Methods: Pilot study performed on 12 RA patients compared to 6 controls affected by osteoarthritis. After the DNA extraction, a universal PCR was made on each sample with 6 couples of primers, covering the whole hypervariable regions of 16S DNA. Each step was performed in strict conditions of sterility to avoid contamination, and several negative controls were used during the whole procedure. Each PCR product was then sequenced on GAIIx Illumina sequencer. Bio-informatic analysis allowed us to identify bacterial flora in each patient sample. An analysis of bacterial DNA repartition was performed for each specimen, and by group of diagnosis. Results: Final analysis was performed on 16 patient samples. One sample (from an OA patient) was removed due to technical process difficulties, another was reclassified because the patient was suffering from recurrent monoarthritis and not RA. Bacterial DNA was found in all samples analyzed, corresponding to a wide range of commensal species from the 4 classical phyla of human microbiome (firmicutes, bacteroidetes, actinobacteria and proteobacteria). Differences between RA patients and controls were observed in the bacterial species diversity and nature. Among these differences, the most important ones were some species only found in RA patients samples: Mycoplasma, Clostridia, Pseudomonas and Burkholderiae species, mostly bacteria potentially pathogenic from the respiratory or intestinal tract. Interestingly, a restricted bacterial diversity was observed in the SF sample of the patient with recurrent monoarthritis, with up to 85% of DNA from a mycoplasma species. Conclusions: Some particularities have been found in the diversity of bacterial species identified in SF from RA patients compared to OA patients. The species identified specifically from SF of RA patients are indicative of a pulmonary or intestinal origin. Bacterial DNA identification does not allow to conclude on germs viability within the joint. Nevertheless, as bacterial DNA may be responsible of dendritic cells activation via TLRs, this study asks the question of the role of bacterial antigens in the triggering of arthritis in RA pathophysiology. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4999